ADVOKASI DAN KOMUNIKASI KEBIJAKAN TRANSFORMASI DESA DI KABUPATEN BUNGO - Jaya, Mulia (Universitas 17 Agustus 1945 Surabaya, 2025)
This study investigates the dynamics of advocacy and policy communication in the transformation of village administrative identity in Bungo Regency, Jambi Province. Changes in terms such as “Village Head to Rio”, “Village to Dusun”, and “Dusun to Kampung” have triggered tensions between the formal bureaucratic structure and the traditional socio-cultural systems. Employing a qualitative case study approach, the research reveals that community resistance stems not only from the policy content but also from the lack of two-way communication and limited participation of local actors in the policy-making and implementation processes. The study identifies instances of hybrid governance in which formal and customary institutions collaborate in governance practices. The findings underscore the importance of more participatory, community-based, and culturally sensitive advocacy and communication strategies to enhance public legitimacy of administrative identity transformation policies in villages. Keywords: Policy Communication, Village Advocacy, Administrative Transformation, Ethnogovernance.Kata Kunci: Komunikasi Kebijakan, Advokasi Desa, Transformasi Administratif, Etnogovernance, Kabupaten Bungo